Experimental investigation on laminar burning velocities of ammonia/hydrogen/air mixtures at elevated temperatures. (1st March 2020) - Lhuillier, Charles; Brequigny, Pierre; Lamoureux, Nathalie; Contino, Francesco; Mounaïm-Rousselle, Christine
Highlights: NH3 /H2 /air laminar burning velocities measured at high temperatures (up to 200 °C). Comparison with a laminar burning velocity correlation from the literature. The promoting effect of the temperature is well captured by the correlation. The effect of the mixture composition is not well captured by the correlation. Correlations to be improved thanks to updated reaction mechanisms and experiments. Abstract: The present study introduces new laminar burning velocity data for ammonia/hydrogen/air mixtures measured by means of the outwardly propagating spherical flame method at atmospheric pressure, for previously unseen unburned gas temperatures ranging from 298 to 473 K, hydrogen fractions ranging from 0 vol% to 60 vol% in the fuel and equivalence ratios in the range [0.8–1.4]. Results show increasing velocities with increasing hydrogen fraction and temperature, with maximum values obtained for rich mixtures near stoichiometry. The new experimental dataset is compared to dedicated laminar burning velocity correlations from the literature and to simulations using detailed kinetic mechanisms. The ammonia/air correlation presents a good agreement with measurements over the whole range of experimental conditions. The ammonia/hydrogen/air correlation captures the effect of the initial temperature satisfactorily for equivalence ratios below 1.3 and hydrogen fractions below 50 vol% in the fuel, but discrepancies are observed in other conditions. The effect of hydrogen addition is reproduced satisfactorily for hydrogen fractions between 20 and 40 vol% in the fuel, but discrepancies are observed for rich mixtures below 20 vol% hydrogen and for all mixtures containing 50 vol% hydrogen and more. An optimization of both correlations is proposed thanks to the experimental data obtained, but only with partial improvement of the ammonia/hydrogen/air correlation. State-of-the-art detailed kinetic reaction mechanisms yield values in close agreement with the present experiments. They could thus be used along with additional experimental data from different techniques to develop more accurate correlations for time-effective laminar burning velocity estimates of NH3 /H2 /air mixtures.